Optimization of tax burden (Farabi Journal of Social Sciences, 2019)
Abstract. The bases of national tax systems should be considered depending on the state of the economic and sociopoliticalstructure in the conditions of market reforms. Thus, the special place in creating a tax systemof market typeare the principles of its construction. If under the tax system the totality of taxes considered, duties and charges leviedon the territory of the state in accordance with the Tax code, and a set of rules and regulations that define the authorityand responsibility of the parties involved in tax transactions. In addition, particularly the importance of practicing theprinciples of the tax system in relation to the characteristics of the development of the state. The emergence of a fundamentallydifferent model of interaction between government and business entities in the field of taxation has determinedthe necessity for consideration of the tax component in the total economic strategy of the enterprises. In this regard,there is a need of economic agents in the formation of individual tax policies that address issues the optimization of taxburden. However, despite the urgency of research influenceof the tax.